1991
DOI: 10.5636/jgg.43.613
|View full text |Cite
|
Sign up to set email alerts
|

North-South Asymmetry in Geomagnetic Activity during the Epoch 1964-1984.

Abstract: A detailed analysis of the indices An and As of geomagnetic activity is made to bring out the nature of the North-South asymmetry in geomagnetic activity. A 10% excess activity in the northern hemisphere is shown to be a real feature for all the years in the epoch . Seasonal variation in the asymmetry exhibits the expected northern summer (winter) maximum for the positive (negative) asymmetry. Equinoxial maxima for marginally positive asymmetry is also shown. A well-defined Universal-Time daily variation is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…So, the interplanetary medium and the terrestrial magnetic field respond to most of solar parameters and their evolution, and any change for activity of these solar parameters between the northern and southern hemispheres may reflect another change on the interplanetary parameters and the geomagnetic indices. Studies by Rangarajan [16] revealed that the sun's northern hemisphere is, almost always, geomagnetically more active, on the average of about 20%, than the southern hemisphere. This enhancement activity may be attributed to the inverse relationship between the geomagnetic activity and the strength of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…So, the interplanetary medium and the terrestrial magnetic field respond to most of solar parameters and their evolution, and any change for activity of these solar parameters between the northern and southern hemispheres may reflect another change on the interplanetary parameters and the geomagnetic indices. Studies by Rangarajan [16] revealed that the sun's northern hemisphere is, almost always, geomagnetically more active, on the average of about 20%, than the southern hemisphere. This enhancement activity may be attributed to the inverse relationship between the geomagnetic activity and the strength of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…In the earlier paper (RANGARAJAN, 1991), the asymmetry in geomagnetic activity was defined as: Fig. 1(b).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, RANGARAJAN (1991) carried out a detailed analysis of the north-south asymmetry in geomagnetic activity for the epoch 1964-84 and showed that though the northern hemisphere has, in general, greater magnitude of geomagnetic activity leading to a positive asymmetry, there are several occasions when the southern hemisphere is more active as evidenced by the magnitude of the negative asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Geomagnetic activity indices are important products derived from observatory magnetometer time series (e.g., Mayaud, 1980; Rangarajan, 1989). Among the oldest and most frequently used are local K indices (e.g., Menvielle & Berthelier, 1991).…”
Section: Geomagnetic Indicesmentioning
confidence: 99%